Upaya Memaksimalkan Potensi Bisnis UMKM melalui Pendampingan Pemasaran Digital - Hardyansah, Rommy; Didit Darmawan; Jahroni; Arifin, Samsul; Negara, Dharma Setiawan; Wibowo, Agung Satryo; Evendi, Wakid; Ikhwanuddin; Rizky, Muchamad Catur; Halizah, Siti Nur; Nuraini, Reny (Forum Kerjasama Pendidikan Tinggi, 2024)
The rapid development of digital technology and the internet has had a significant impact on marketing, especially for Micro, Small and Medium Enterprises (MSMEs). Digital marketing is a more promising option because it allows potential customers to get complete information about products and make transactions online. Although it is still considered less important by the players, this is due to the need for specialized skills related to mastering information technology in order to reach a larger target market. Previously, the sale of Makaroni New Asep required consumers to come directly to see the products they wanted to buy. The purpose of this research is to provide an understanding to the owner of Makaroni New Asep Micro, Small and Medium Enterprises (MSMEs) regarding the implementation of digital marketing strategies. In an effort to provide guidance to Makaroni New Asep Micro, Small and Medium Enterprises (MSMEs) regarding the application of Digital Marketing as a product marketing strategy, this activity involves several stages, including: (1) introduction to the use of social media; (2) introduction to the marketplace platform; and (3) the process of receiving orders and shipping goods. The results of this service show that New Asep Macaroni MSMEs now have a significant presence on social media and the marketplace. MSME owners also gained a better understanding of digital marketing and managed social media and marketplace platforms effectively. Thus, this community service contributes to increasing the competitiveness of MSMEs in facing the digital marketing era.